Surface and interface chemistry of clay minerals - Schoonheydt, Robert; Johnston, C. T.; Bergaya, Faiza (Developments in clay science, 2018)
Surface and Interface Chemistry of Clay Minerals, Volume 9, delivers a fundamental understanding of the surface and interface chemistry of clay minerals, thus serving as a valuable resource for researchers active in the fields of materials chemistry and sustainable chemistry. Clay minerals, with surfaces ranging from hydrophilic, to hydrophobic, are widely studied and used as adsorbents. Adsorption can occur at the edges and surfaces of clay mineral layers and particles, and in the interlayer region. This diversity in properties and the possibility to tune the surface properties of clay minerals to match the properties of adsorbed molecules is the basis for study. This book requires a fundamental understanding of the surface and interface chemistry of clay minerals, and of the interaction between adsorbate and adsorbent. It is an essential resource for clay scientists, geologists, chemists, physicists, material scientists, researchers, and students.